POLA BERTANI PADI LADANG PADA MASYARAKAT TOLAKI ( STUDI ANTROPOLOGI DI KELURAHAN ALANGGA KECAMATAN ANDOOLO KABUPATEN KONAWE SELATAN ) - Ida Juliani; Syam sumarlin; Rahmat Sewa Suraya (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2018)
This research aimed to find out and to describe the dry field paddy farming system ritually related to the dry field farming pattern in Tolaki community in Kelurahan Alangga (Alangga Village) of Andoolo Sub District of Konawe Selatan (South Konawe) Regency, using Wolf’s (1983) farmer ecotype theory. This study used descriptive approach. The result of research revealed the followings. (1) Tolaki community in Kelurahan Alangga used some stages in doing dry field paddy farming. By the availability of land, the type of farmer is divided into two: the farmers cultivating the land themselves and the ones cultivating the land by borrowing land from land owner. Meanwhile, seed procurement was conducted by means of buying it, because the paddy variety planted by Tolaki community in Kelurahan today is different from that in the past. Then, land cultivation was conducted in some stages: clearing away, burning, and cleaning the burning remains. Next, hut development, fence development, planting, plant maintenance, and harvesting, and post-harvesting were conducted. Tolaki people in Kelurahan Alangga did dry field farming to satisfy household economy. (2) There were two rites related to dry field farming pattern in Tolaki community: mombodai and mombongu. It was conducted hereditarily by the people living in Kelurahan Alangga. From the result of research, it could be concluded that (1) dry field farming system in Kelurahan Alanga was conducted in patterned manner corresponding to the ancestor’s tradition maintained until today, despite many farmers using modern farming system, and (2) the rite related to dry field farming pattern was still conducted in Kelurahan Alangga, because the people still believed that the rite would affect positively the paddy they plant and their harvest.